Awareness and use of biodiversity collections by fish biologists. Issue 2 (20th December 2019) - Singer, Randal A.; Ellis, Shari; Page, Lawrence M.
Abstract: A survey of 280 fish biologists from a diverse pool of disciplines was conducted in order to assess the use made of biodiversity collections and how collections can better collect, curate and share the data they have. From the responses, data for how fish biologists use collections, what data they find the most useful, what factors influence the decisions to use collections, how they access the data and explore why some fish biologists make the decision to not use biodiversity collections is collated and reported. The results of which could be used to formulate sustainability plans for collections administrators and staff who curate fish biodiversity collections, while also highlighting the diversity of data and uses to researchers.